Binary Opposition of Eros and Thanatos in Wordsworth’s "The Rainbow" - Datta, Vijay Kumar; Pandey, Beerendra (Journal of Advanced Academic Research, 2018)
William Wordsworth’s most quintessential, oeuvre-defining ode—“The Rainbow”—is unjustifiably under-commented in literary criticisms on the British Romantic poet. Plugging this critical gap, an attempt has been made to make a full-fledged critical analysis of the dynamics of the Freudian concepts of eros and thanatos in the poem. This analysis has been undertaken to make the argument that the dialectical play, which is finally resolved in favour of life-drive, helps sustain the poet’s life-long joyful communion with Nature, despite the threats of trauma and tentativeness to bog him down.